Materialising Oceania: New ethnographies of things in Melanesia and Polynesia - Bell, Joshua A. (The Australian journal of anthropology, 2009)
Oceania occupies an intriguing place within anthropology’s genealogy. In the introduction to this collection of essays, we examine the role of the ethnography of Oceania in the development of our anthropological perspectives on materialisation, the dynamic process by which persons and things are inter-related. Building upon the recent resurgence of theoretical interests in things we use the term materialisation (rather than material culture or materiality) to capture the vitality of the lived processes by which ideas of objectivity and subjectivity, persons and things, minds and bodies are entangled. Taking a processual view, we advocate for an Oceanic anthropology that continues to engage with things on the ground; that asks what strategies communities use to materialise their social relations, desires and values; and that recognises how these processes remain important tools for understanding historical and contemporary Oceanic societies. Examining these locally articulated processes and forms contributes to a material (re)turn for anthropology that clarifies how we, as scholars, think about things more widely.